The Effect of Brand Image, Price and Product Quality on Purchasing Decisions for Iphone Products - Sari, Indah Mutiara; Asral, A. (Manunggal Halim Jaya, 2025)
This study is designed to examine the impact of Brand Image, Price, and Product Quality on Purchasing Decisions for iPhone products, especially in competition with other brands. The increasingly competitive condition of the cellphone market, especially with the emergence of iPhone products as a basic necessity in an ever-growing era, also affects the company's strategy for maintaining its position in the market. In addition, this study also aims to identify the most dominant factor influencing the purchase decision of iPhone products between Brand Image, Price, or Product Quality. The survey method was chosen to collect information from 96 respondents of potential iPhone product users at Universitas Pelita Bangsa, specifically from the class of 2020 students at the Faculty of Economics, Business Management Study Program. In this research, the approach applied is quantitative, using questionnaires and literature studies as data collection techniques. Data analysis was carried out through several methods, including validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. Based on the t-test results, a calculated t-value of 2.861 with a significance level of 0.005 was obtained, indicating acceptance of the initial hypothesis. This confirms the significant and positive effect of brand image on purchasing decisions. The t-test results on the price variable produced a t-value of 8.009 with a significance level of 0.00, which indicates that the second hypothesis is accepted. This shows that price partially has a positive and significant influence on purchasing decisions. Meanwhile, the product quality variable obtained from the t-test results shows a calculated t-value of 2.022 with a significance of 0.046, stating the acceptance of the third hypothesis and indicating a positive and significant effect of product quality on purchasing decisions. Based on these findings, it can be concluded that 81.5% of purchasing decisions are influenced by a combination of brand image, price, and product quality variables, while the other 18.5% are influenced by other variables not examined in this study.